Analisis Pengendalian Persediaan Bahan Habis Pakai Chemical dan Fertilizer Dalam Upaya Efisiensi Biaya pada PT Batamindo Executive Village - Aulia Utami (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
The purpose of this study was to determine the availability of inventory purchases of consumables and efforts made to streamline inventory costs. Data collection techniques used were observation and interviews, the analysis method used is descriptive analysis method. From interviews, observation can be concluded that the supply of consumables chemical and fertilizer nor any efficiency cost of inventory is running efficiently with the purchasing policy once every three months